The clinical phenotype of early‐onset isolated dystonia caused by recessive COL6A3 mutations (DYT27). Issue 5 (21st December 2015) - Jochim, Angela; Zech, Michael; Gora‐Stahlberg, Gina; Winkelmann, Juliane; Haslinger, Bernhard
ABSTRACT: Background and Purpose: We recently identified mutations in the a3 (VI) collagen gene COL6A3 that cause autosomal‐recessive isolated dystonia (DYT27). This article gives a detailed description of the clinical phenotype associated with this new type of dystonia. Methods: A total of 5 recessive COL6A3 mutation carriers underwent clinical examinations, and case histories were recorded on videotape. Results: Biallelic COL6A3 mutations cause isolated dystonia with interindividual heterogeneity of distribution and severity. Dystonia was generalized in 3 patients, pronounced in the cranio‐cervical region, upper limbs, and trunk; segmental in 1 patient, with the neck and upper limbs affected; and focal with cervical involvement in another patient. Symptoms began in childhood, adolescence, or early adulthood, initially affecting the neck as cervical dystonia or the hand as writer's cramp. Conclusion: COL6A3 ‐associated dystonia represents a newly identified autosomal‐recessive entity characterized clinically by an early symptom onset with variable distribution. © 2015 Movement Disorder Society